Place-Names in the Polar Regions - Debenham, Frank (Polar Record, 1942)
To many people looking for the first time at maps of the polar regions it seems astonishing how lacking in originality many of the names appear to be. Yet, before they become too trenchant in their criticism they should themselves try the experiment of finding names for the natural features which they see round them. It is not as easy as it sounds, and however firmly one lays down rules for place-names they will be broken over and over again with good reasons.